2016
DOI: 10.3390/app6010022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Heating Process on the Photoluminescence Properties of Perovskite Eu-Doped BaZrO3 Powder

Abstract: Abstract:In this study, BaZrO 3 :Eu 0.025 powder was synthesized through the solid-state reaction method with two different heating processes. For the one-step process, the BaZrO 3 :Eu 0.025 powder was heated to 1000˝C-1400˝C for 2 h. For the two-step heating process, the BaZrO 3 :Eu 0.025 powder was pre-heated at 800˝C for 2 h, after being cooled to room temperature and ground, then the powder was heated to 1000˝C-1400˝C again for 2 h. The optimum excitation optical wavelength of BaZrO 3 :Eu 0.025 powders wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…These previous results [6,16], and the results this study, suggest that the transitions of Eu 3+ ions between different energy bands are affected by the host materials of the prepared phosphors.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…These previous results [6,16], and the results this study, suggest that the transitions of Eu 3+ ions between different energy bands are affected by the host materials of the prepared phosphors.…”
Section: Resultssupporting
confidence: 76%
“…Liu and Wang's research also showed that the emission intensities of 5 D0-7 F0 (576 nm), 5 D0-7 F1 (597 nm), and 5 D0-7 F2 (616, 623 nm) had almost the same values, even if the Eu concentration in the BaZr1−xEuxO3 phosphor powders was different [26]. These previous results [6,16], and the results this study, suggest that the transitions of Eu 3+ ions between different energy bands are affected by the host materials of the prepared phosphors.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, europium embedded in low phonon glasses is characterized by a high emission efficiency in the visible range as a result of wide energy gap (approx. ∆E = 12,000 cm −1 ) between the D 0 emitting state and the 7 F J ground multiplet [7,8]. The advantage of the Eu 3+ ion is also its common use as a spectroscopic probe of the site symmetry in different host matrices [9,10].…”
Section: Introductionmentioning
confidence: 99%